2018
DOI: 10.1176/appi.ajp.2018.17060720
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intranasal Esketamine for the Rapid Reduction of Symptoms of Depression and Suicidality in Patients at Imminent Risk for Suicide: Results of a Double-Blind, Randomized, Placebo-Controlled Study

Abstract: These preliminary findings indicate that intranasal esketamine compared with placebo, given in addition to comprehensive standard-of-care treatment, may result in significantly rapid improvement in depressive symptoms, including some measures of suicidal ideation, among depressed patients at imminent risk for suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
203
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 557 publications
(213 citation statements)
references
References 33 publications
5
203
1
4
Order By: Relevance
“…Thus, this unique “5‐min administration” technique using a relatively lower dose of 0.2 mg/kg may enable widespread emergency department usage. In addition, our findings are similar to other studies conducted in the emergency department (Burger et al, ; Grunebaum et al, ; Kashani et al, ; Larkin & Beautrais, ) and are similar to the results attained for esketamine (Canuso et al, ). The unexpected lack of a statistically significant reduction in the depressive score is similar to other studies that evaluated ketamine for suicidal ideation and considered depression as a secondary outcome (Grunebaum et al, ; Murrough et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, this unique “5‐min administration” technique using a relatively lower dose of 0.2 mg/kg may enable widespread emergency department usage. In addition, our findings are similar to other studies conducted in the emergency department (Burger et al, ; Grunebaum et al, ; Kashani et al, ; Larkin & Beautrais, ) and are similar to the results attained for esketamine (Canuso et al, ). The unexpected lack of a statistically significant reduction in the depressive score is similar to other studies that evaluated ketamine for suicidal ideation and considered depression as a secondary outcome (Grunebaum et al, ; Murrough et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Ketamine, a glutamatergic modulator and a rapidly acting antidepressant (aan het Rot et al, 2010;Berman et al, 2000;Domany et al, 2018;Murrough et al, 2013;Singh et al, 2016;Zarate et al, 2006), has been shown to rapidly reduce suicidal ideation (Grunebaum et al, 2018;Ibrahim et al, 2011;Price, Nock, Charney, & Mathew, 2009). In addition, esketamine, the S enantiomer of racemic ketamine, has shown similar results (Canuso et al, 2018). Ketamine's antisuicidal properties raised interest in the emergency department settings, where it was evaluated in open-label trials (Larkin & Beautrais, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It might well be that CAMS is optimal for the largest proportion of patients with a history of SI but not SA, whereas other SRB‐focused interventions are optimal among patients with a history of prior SAs. Given the focus of both CAMS and recently approved intranasal esketamine on rapid reduction in SI (Canuso et al, ), it would be of special interest to compare the separate and joint effects of these two treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A number of prior studies have attempted to combine multiple interactions along the same basic lines as we do here to develop composite PTRs for treatment of major depression (reviewed by Cohen & DeRubeis, 2018). Similar efforts are also beginning to appear in studies of other mental disorders (e.g., Fernandes et al, 2017;van den Oord, Chan, & Aberg, 2018).…”
mentioning
confidence: 94%
“…Initial case reports (Dwyer et al, 2017) and a small open-label trial (Cullen et al, 2018) have suggested possible efficacy in pediatric populations, although there are currently no published randomized, controlled trials evaluating efficacy in pediatric populations. Recently, the FDA has approved esketamine (an intranasally delivered formulation of the l-enantiomer of ketamine) for the treatment of treatmentrefractory depression in adults (Singh et al, 2016) and initial studies have suggested that esketamine may also be effective acutely in reducing suicidal ideation (Canuso et al, 2018). Trials examining the efficacy of ketamine (NCT02579928 and NCT03889756) and esketamine (NCT03185819) in pediatric depression populations are currently ongoing.…”
Section: Interventional Treatmentsmentioning
confidence: 99%